The Effect of Massage Gun and Ice Bath on the Recovery of Young National Athletes: Feminine and Masculine Perspectives of Program Implementation from January to June 2025 - Ridha Mustaqim; Berliana Berliana; Hadiat Aliansyah; Tian Kurniawan; Tono Haryono (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
Fatigue is a common consequence of high-intensity sports and cannot be resolved by rest alone, as it relates to energy metabolism. It can be categorized into physical and mental fatigue, with symptoms such as Delayed Onset Muscle Soreness (DOMS), muscle and joint pain, reduced flexibility, cramps, swelling, and inflammation. Recovery is therefore crucial in training, as it promotes cell regeneration, prevents injuries, and reduces lactic acid buildup, which serves as an indicator of fatigue. This study investigates the effects of ice bath and massage gun methods on recovery in young national taekwondo and gymnastics athletes. An experimental pretest-posttest control group design was applied to 18 purposively selected athletes training under the Ministry of Youth and Sports. Blood lactate levels were measured objectively through blood sampling, while pain perception was assessed subjectively using the Visual Analog Scale (VAS). Sport-specific fatigue patterns were considered, with taekwondo athletes showing predominantly lower-body DOMS (100% legs), while gymnastics athletes presented a balanced distribution (50:50). Results demonstrated that both recovery methods significantly reduced lactic acid levels, as reflected in lower VAS scores. In conclusion, ice bath and massage gun treatments provide effective recovery strategies to support performance maintenance in young athletes.